Parents' acceptance to vaccinate children against COVID-19: A Syrian online survey - Swed, Sarya; Alibrahim, Hidar; Bohsas, Haidara; Shoib, Sheikh; Hasan, Mohammad Mehedi; Motawea, Karam R.; Albuni, Mhd Kutaiba; Battikh, Elias; Sawaf, Bisher; Elkalagi, Nashaat Kamal Hamdy; Mohamed Alsharief Ahmed, Safaa; Mohammed Sharif Ahmed, Eman; et al. (Frontiers in Public Health, 2022)
After the widespread of COVID-19 virus worldwide, vaccination targeted reducing spread of cases and mortality rates. However, vaccination hesitancy was observed among the communities worldwide. Vaccination hesitancy involved parents regarding the decision of vaccinating their children- After obtaining ethical approval, an online cross-sectional study was conducted from 1 March to 22 April 2021 to evaluate the parents' acceptance of vaccinating their children against the COVID-19 virus in Syria. Data were analyzed using descriptive and multivariate logistic regression analysis in IBM, SPSS V. 28.0 package program (IBM Corporation, Armonk, NY, USA). Among 283 participants, 105 participants agreed to vaccinate their children, and 178 were not. A significant correlation between age and vaccine willingness was found (P-value < 0.0001*), especially in the age group between 18 and 30 years old (45.2%). Parents who accepted vaccinating themselves were more willing to vaccinate their children (34.6%). According to our results, there is a greater need to enhance awareness and knowledge programs about the vaccine's effectiveness and encourage parents to accept giving the vaccine to their children.